Volker Bach: The Kitchen, Food, and cooking in Reformation Germany - MacDonogh, Giles (Petits Propos Culinaires, 2017)
Volker Bach: The Kitchen, Food, and cooking in Reformation Germany: Rowman & Littlefield, 2016: 218 pp., hardback, £69.45.